Pengaruh Pembinaan Disiplin dan Keselamatan dan Kesehatan Kerja (K3) terhadap Kepuasan Kerja Karyawan Divisi Stamping Bagian Produksi-1 PT. Xyz - Sera Ambarwati; R.M. Juddy Prabowo (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the effect of discipline coaching and occupational safety and health (K3) on employee job satisfaction in the Stamping Division of Production Section-1 of PT. XYZ. The approach used is quantitative by distributing questionnaires to 76 employees who have worked for at least one year. Data measurement uses a semantic differential scale, and analysis is carried out through validity, reliability, multiple linear regression, coefficient of determination, and partial tests. The results of the study indicate that all instruments are valid (r_count > r_table 0.1901) and reliable (Cronbach's Alpha > 0.60). Descriptively, discipline coaching is in the "quite good" category (mean 3.395), K3 is in the "good" category (mean 3.47), and job satisfaction is in the "quite satisfied" category (mean 3.37). Regression tests show that discipline coaching (β = 0.402) and K3 (β = 0.922) have a positive effect on job satisfaction, with a contribution of 75.1% (R² = 0.751). Partial test shows that both independent variables significantly affect job satisfaction (sig < 0.05). Conclusion, that discipline and K3 coaching play an important role in increasing employee job satisfaction.  Keywords: Discipline Coaching, Occupational Safety and Health, Job Satisfaction, Employees